Zhizhu decoction alleviates slow transit constipation by regulating aryl hydrocarbon receptor through gut microbiota - Yong Wen; Yu Zhan; Shiyu Tang; Fang Liu; Rong Wu; Pengfei Kong; Qian Li; Xuegui Tang (Taylor & Francis Group, 2023)
AbstractContext Slow transit constipation (STC), the most common type of constipation, seriously affects the life of patients. Zhizhu decoction (ZZD), a traditional Chinese medicine compound, has is effective against functional constipation, but the mechanism is still unclear.Objective This research explores the mechanism of ZZD on STC from the perspective of metabolomics and gut microbiota.Materials and methods Fifty-four C57BL/6 mice were randomly divided into six groups (n = 9): control (control); STC (model); positive control (positive); low-dose (5 g/kg; L-ZZD), medium-dose (10 g/kg; M-ZZD), and high-dose (20 g/kg; H-ZZD) ZZD treatment. Following treatment of mice with ZZD for two weeks, the changes in intestinal motility, colon histology, intestinal neurotransmitters, and aryl hydrocarbon receptor (AHR) pathway determined the effects of ZZD on the pathophysiology of STC. LC-MS targeting serum metabolomics was used to analyze the regulation of ZZD on neurotransmitters, and 16S rRNA high-throughput sequencing was used to detect the regulation of the gut microbiome.Results ZZD had the highest content of naringin (6348.1 mg/L), and could significantly increase the 24 h defecations (1.10- to 1.42-fold), fecal moisture (1.14-fold) and intestinal transport rate (1.28-fold) of STC mice, increased the thickness of the mucosal and muscular tissue (1.18- to 2.16-fold) and regulated the neurotransmitters in the colon of STC mice. Moreover, ZZD significantly activated the AHR signaling pathway, and also affected the composition of gut microbiota in STC mice.Discussion and conclusions The beneficial effect and the possible mechanism of ZZD on STC could provide a theoretical basis for the broader clinical application of ZZD.